MODERN TENDENCIES IN ORGANIZING THE INNOVATIVE ACTIVITY OF THE TEACHER - Bobonazarova Sevara Odil qizi (American Journals, 2024)
This article talks about modern approaches to organizing the activities of a preschool educational organization and the trends encountered along this path, as well as measures to eliminate them. Also, the effective implementation of a teacher’s innovative activities depends on a number of conditions, such as the teacher’s unbiased attitude towards opposing opinions, his willingness to express recognition of the rational situation in various situations, as a result of which the teacher improves. his knowledge and scientific activity such issues as the presence of an overarching theme (motive) providing.
Keywords: Preschool education, trend, conflict, problem, innovative approach, independent thinking, form, method, tool.